Chemically-defined generation of human hemogenic endothelium and definitive hematopoietic progenitor cells. (June 2022) - Chang, Yun; Syahirah, Ramizah; Oprescu, Stephanie N.; Wang, Xuepeng; Jung, Juhyung; Cooper, Scott H.; Torregrosa-Allen, Sandra; Elzey, Bennett D.; Hsu, Alan Y.; Randolph, Lauren N.; Sun, Yufei; Kuang, Shihuan; et al.
Abstract: Human hematopoietic stem cells (HSCs), which arise from aorta-gonad-mesonephros (AGM), are widely used to treat blood diseases and cancers. However, a technique for their robust generation in vitro is still missing. Here we show temporal manipulation of Wnt signaling is sufficient and essential to induce AGM-like hematopoiesis from human pluripotent stem cells. TGFβ inhibition at the stage of aorta-like SOX17 + CD235a − hemogenic endothelium yielded AGM-like hematopoietic progenitors, which closely resembled primary cord blood HSCs at the transcriptional level and contained diverse lineage-primed progenitor populations via single cell RNA-sequencing analysis. Notably, the resulting definitive cells presented lymphoid and myeloid potential in vitro ; and could home to a definitive hematopoietic site in zebrafish and rescue bloodless zebrafish after transplantation. Engraftment and multilineage repopulating activities were also observed in mouse recipients. Together, our work provided a chemically-defined and feeder-free culture platform for scalable generation of AGM-like hematopoietic progenitor cells, leading to enhanced production of functional blood and immune cells for various therapeutic applications.